PERANAN MODAL SOSIAL BAGI PETANI MISKIN UNTUK MEMPERTAHANKAN KELANGSUNGAN HIDUP RUMAH TANGGA DI PEDESAAN NGAWI (STUDI KASUS DI DESA RANDUSONGO KECAMATAN GERIH KABUPATEN NGAWI PROVINSI JAWA TIMUR) - Saheb Saheb; Yulius Slamet; Ahmad Zuber (Jurnal Analisa Sosiologi, 2013)
This study was a descriptive qualitative research aiming to describe the role of Social Capital for the poor farmer to sustain their household life. The subject of research consisted of poor farmers having a less-than-0.13 ha land conducted in RT 4 RW 6 Bulu II Hamlet, Randusongo Village, Gerih Subdistrict, Ngawi Regency, East Java Province.This study was conducted using in-depth interview, observation, and library study techniques. Meanwhile, the sampling technique used was maximum variation sampling taken seven informants as the sample, consisting of four informants: poor old, very poor old, poor young, and very poor young farmers, as the case informant, while the key informant of research consisted of: elders of Randusongo Village, Carik/Secretary of Randusongo Village, and Head of Bulu II Hamlet. Key informant was also used as the instrument of validating the field data from the informant.The case informants were selected based on the criterion specified by Statistical Central Agency (BPS), that was, those belonging to poor family, while key informants were the village elders considered as knowledgeable and understanding about the daily condition of poor farmers because they domiciled in the same hamlet, and the village apparatus considered as knowing the poor farmers’ condition because they often gave them service regarding Bantuan Langsung Tunai ((BLT= Cash Direct Grant) now called Bantuan Langsung Sementara Masyarakat (BLSM = Temporary Public Grant), Raskin (rice for poor people) and other services.The result showed that bonding social capital played an important role for the poor farmers in sustaining their household life. It could be seen from those helping their poor close relatives in meeting their daily life needs. Bridging social capital is the strongest out of the three social capitals existing because many poor farmer household could survive because of their close neighbor’s help. Linking social capital did not play a role at al because such organization as PKK (Pendidikan Kesejahteraan Keluarga = Family Welfare Education) or organization at either RT or RW level in Randusongo village did not work thereby could not contribute to reinforcing social capital within the society. Keywords : social capital, poor farmer, life sustainability